Long-life in-situ temperature field monitoring using Fiber Bragg grating sensors in electromagnetic launch high-rate hardcase lithium-ion battery. (January 2023) - Wu, Yiting; Long, Xinlin; Lu, Junyong; Zhou, Ren; Liu, Lang; Wu, Yangyang
Abstract: High-rate hardcase lithium-ion batteries used in electromagnetic launch(EML) applications operate under continuous high-current pulse conditions, accompanied by intense heat generation and large internal temperature gradients. Accurate detection of the characteristics of their internal temperature field is difficult using conventional temperature measurement methods, which in turn causes difficulties in defining their safe-use boundaries. In this paper, we proposed a method for embedding long-life optical fiber grating temperature sensors inside a high-rate hardcase lithium-ion battery to achieve long-period in-situ detection of the temperature field inside the battery. The room temperature aging study and constant current charge/discharge results showed no significant difference in performance between the two sensors-embedded batteries and the same batch of battery after 20 months of preparation. The temperature calibration results showed that the relative error of temperature measurement of the ten embedded fiber grating temperature sensors did not exceed 0.5 K at all 3 stages. This test data can guide optimal design and guarantee the ultimate safe use of the high-rate battery. Highlights: In-situ internal temperature field monitoring realized by multiple fiber-Bragg-grating sensors. Sensors' accuracy and battery performance were not influenced one year after placement. Battery temperature field distribution and revolution observed under high power pulse discharge. Surrounding cooling is more effective than frontal cooling for high-power batteries.